Dysbiosis of Gut Microbiome Is Associated With Rupture of Cerebral Aneurysms. Issue 3 (March 2022) - Kawabata, Shuhei; Takagaki, Masatoshi; Nakamura, Hajime; Oki, Hiroya; Motooka, Daisuke; Nakamura, Shota; Nishida, Takeo; Terada, Eisaku; Izutsu, Nobuyuki; Takenaka, Tomofumi; Matsui, Yuichi; Yamada, Shuhei; et al.
Abstract : Background and Purpose: Environmental factors are important with respect to the rupture of cerebral aneurysms. However, the relationship between the gut microbiome, an environmental factor, and aneurysm rupture is unclear. Therefore, we compared the gut microbiome in patients with unruptured intracranial aneurysms (UIAs) and ruptured aneurysms (RAs) to identify the specific bacteria causing the rupture of cerebral aneurysms. Methods: A multicenter, prospective case-control study was conducted over one year from 2019 to 2020. The fecal samples of patients with stable UIAs and RAs immediately after onset were collected. Their gut microbiomes were analyzed using 16S rRNA sequencing. Subsequently, a phylogenetic tree was constructed, and polymerase chain reaction was performed to identify the specific species. Results: A total of 28 RAs and 33 UIAs were included in this study. There was no difference in patient characteristics between RAs and UIAs: age, sex, hypertension, dyslipidemia, diabetes status, body mass index, and smoking. No difference was observed in alpha diversity; however, beta diversity was significantly different in the unweighted UniFrac distances. At the phylum level, the relative abundance of Campylobacter in the RA group was larger than that in the UIA group. Furthermore, the gut microbiome in the RA and UIA groups exhibited significantly different taxonomies. However, Campylobacter was focused on because it is widely known as pathogenic among these bacteria. Then, a phylogenetic tree of operational taxonomic units related to Campylobacter was constructed and 4 species were identified. Polymerase chain reaction for these species identified that the abundance of the genus Campylobacter and Campylobacter ureolyticus was significantly higher in the RA group. Conclusions: The gut microbiome profile of patients with stable UIAs and RAs were significantly different. The genus Campylobacter and Campylobacter ureolyticus may be associated with the rupture of cerebral aneurysms. Abstract : Supplemental Digital Content is available in the text.